Determination of binary mixture of ibuprofen and famotidine by different spectrophotometric methods - Al-Shibly, Ahmed Aqeel; Monir, Hany Hunter; El-Ghobashy, Mohamed Refaat; Amer, Sawsan Mohamed (European Journal of Chemistry, 2016)
Four simple and specific spectrophotometric methods were developed and validated for the simultaneous determination of binary mixture of ibuprofen and famotidine, using unified regression equation. The proposed spectrophotometric procedures including, derivative ratio, ratio subtraction, dual wavelength and mean centering of ratio spectra do not require any separation steps. Accuracy, precision and linearity ranges of the proposed methods were determined and the specificity was assessed by analysing synthetic mixtures of both drugs. The methods were applied to a pharmaceutical formulation and the results obtained showed that there is no significant difference between the proposed methods and the reported one regarding both accuracy and precision.